Understory species composition mediates soil greenhouse gas fluxes by affecting bacterial community diversity in boreal forests - Duan, Beixing; Xiao, Ruihan; Cai, Tijiu; Man, Xiuling; Ge, Zhaoxin; Gao, Minglei; Mencuccini, Maurizio (Frontiers in Microbiology, 2023)
Introduction Plant species composition in forest ecosystems can alter soil greenhouse gas (GHG) budgets by affecting soil properties and microbial communities. However, little attention has been paid to the forest types characterized by understory vegetation, especially in boreal forests where understory species contribute significantly to carbon and nitrogen cycling. Method In the present study, soil GHG fluxes, soil properties and bacterial community, and soil environmental conditions were investigated among three types of larch forest [Rhododendron simsii-Larix gmelinii forest (RL), Ledum palustre-Larix gmelinii forest (LL), and Sphagnum-Bryum-Ledum palustre-Larix gmelinii forest (SLL)] in the typical boreal region of northeast China to explore whether the forest types characterized by different understory species can affect soil GHG fluxes. Results The results showed that differences in understory species significantly affected soil GHG fluxes, properties, and bacterial composition among types of larch forest. Soil CO2 and N2O fluxes were significantly higher in LL (347.12 mg m−2 h−1 and 20.71 μg m−2 h−1) and RL (335.54 mg m−2 h−1 and 20.73 μg m−2 h−1) than that in SLL (295.58 mg m−2 h−1 and 17.65 μg m−2 h−1), while lower soil CH4 uptake (−21.07 μg m−2 h−1) were found in SLL than in RL (−35.21 μg m−2 h−1) and LL (−35.85 μg m−2 h−1). No significant differences between LL and RL were found in soil CO2, CH4, and N2O fluxes. Soil bacterial composition was mainly dominated by Proteobacteria, Actinobacteria, Acidobacteria, and Chloroflexi among the three types of larch forest, while their abundances differed significantly. Soil environmental variables, soil properties, bacterial composition, and their interactions significantly affected the variations in GHG fluxes with understory species. Specifically, structural equation modeling suggested that soil bacterial composition and temperature had direct close links with variations in soil GHG fluxes among types of larch forest. Moreover, soil NO3−−N and NH4+ − N content also affected soil CO2, CH4, and N2O fluxes indirectly, via their effects on soil bacterial composition. Discussion Our study highlights the importance of understory species in regulating soil GHG fluxes in boreal forests, which furthers our understanding of the role of boreal forests in sustainable development and climate change mitigation.